2022
DOI: 10.1007/s40123-022-00473-3
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Implant for Diabetic Macular Oedema: 1-Year Treatment Outcomes from the Fight Retinal Blindness! Registry

Abstract: Introduction: Phase III clinical trials of dexamethasone intravitreal implant for diabetic macular oedema (DMO) have reported significant improvements in visual acuity (VA). Studies evaluating the treatment of DMO in routine clinical practice provide data to identify areas that need improvement. This study evaluated 12-month treatment outcomes of dexamethasone implant for DMO in routine clinical practice. Methods: Retrospective data analysis of eyes that started dexamethasone implant for DMO from 1 June 2013 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…These improvements align with those observed in other recent real-world studies. [12][13][14][15][16][17] For both outcome measures, peak effectiveness was observed at 6 weeks post-treatment. This is a little earlier than in other analyses, which typically found that the effects of DEX on VA and CMT peaked at 2-3 months.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These improvements align with those observed in other recent real-world studies. [12][13][14][15][16][17] For both outcome measures, peak effectiveness was observed at 6 weeks post-treatment. This is a little earlier than in other analyses, which typically found that the effects of DEX on VA and CMT peaked at 2-3 months.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies found that VA improvements with DEX were greater in patients who were previously treatment-naïve. 10 , 12 , 13 , 15 , 16 On the flipside, a recent analysis of data from an international registry found no effect of prior treatment on VA improvements following DEX injection in 204 patients with DMO; 17 however, the comparison was made at 12 months, which is later than other studies (assessing VA at 1–6 months post-treatment), potentially masking short-term effects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Experimentally, synthetic glucocorticoid, i.e., DEX, is used for the treatment of DR due to its anti-inflammatory and immunological defensive properties [ 69 , 70 ]. PBC also possesses multi-targeted actions, such as DEX, and it protects from cellular oxidative damage in multiple diabetic complications [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The natural astaxanthin has favorable effects against ischemia-reperfusion injury associated with brain damage and neurovascular inflammation [64]. Commercially, the synthetic glucocorticoid, i.e., DEX, is widely used in various inflammatory and immunological disorders including DR [65,66]. AST possesses multi-targeted actions similar to dexamethasone and it protects the retinal blood vessels in diabetic conditions [67].…”
Section: Discussionmentioning
confidence: 99%